The Development of Student Worksheet Based on Problem Based Learning Approach on Matrices Topics - Aneliana, Aneliana; Ditasona, Candra; Manalu, Risma Uly (Brillo Journal, 2022)
This study aims to develop Problem Based Learning (PBL)-based worksheets to improve student’s critical thinking skills in contextual problem solving. The research design used is a feasibility analysis by research and development methods. The research was carried out using research and development (R&D) research and development methods. The sample consisted of 40 students from science programs in 11th grade. The data collection instrument used is the expert assessment sheet, student responses to the created worksheet. The development procedure with 8 stages namely potentials and problems, information gathering, product design, expert validation, first revision, product trial, second revision, final product. From the results obtained the average feasibility value by the media is 81.46% (very feasible), the average graphic feasibility value is 81.85% included in the very feasible criteria, the language eligibility average value is 76% included in the appropriate criteria and the average value of student responses is (87.40%) (very positive).